Kinetics and isotherms of Cu(II) and Hg(II) adsorption onto iron modified montmorillonite / polycaprolactone nanofiber membrane - Cuazon, Ralph C.; Somera, Lester Raj A.
Exposure to toxic concentrations of Cu(II) and Hg(II) ion continues to increase in developing countries due to rapid industrialization. Because of their high solubility in water, Cu(II) and Hg(II) ions from mining and urban runoffs can easily contaminate various water sources. An adsorbent for Cu(II) and Hg(II) ions was fabricated by immobilizing Fe modified montmorillonite particles in polycaprolactone through electrospinning. The SEM images of the fabricated membrane showed a nanofiber network with fiber diameter ranging from 88 nm to 569 nm and an average fiber diameter of 242 nm. Furthermore, potentiometric titration revealed that the fabricated membrane has no point of zero charge and it maintains a dominant negative surface charge throughout pH 2 to 9. The adsorption behavior of the fabricated membrane was investigated using kinetics and isotherm models. The effect of contact time and initial metal ion concentration to the adsorption capacity were also studied. It was found that the adsorption of both Cu(II) and Hg(II) ions onto the membrane follows a pseudo-second order model. Langmuir isotherm and Freundlich isotherm best describes the adsorption behavior of Cu(II) ion and Hg(II) ions, respectively. The adsorption capacities of both ions were found to increase with increasing contact time and with increasing initial metal ion concentration. The highest adsorption capacity of the fabricated membrane for Cu(II) and for Hg(II) ions are 6.44 mg/g and 14.25 mg/g, respectively. Sorption energy was calculated using the Dubinin-Kaganer-Radushkevich isotherm to determine the type of adsorption for both Cu(II) and for Hg(II) ions. The values obtained for Cu(II) and Hg(II) are -5.83 kJmol-1 and -2.68 kJmol-1, respectively. The values suggest that the type of adsorption was physisorption.